2021
DOI: 10.1108/he-07-2021-0105
|View full text |Cite
|
Sign up to set email alerts
|

Role of factors in eHealth literacy in period of COVID-19: a study of Turkey

Abstract: PurposeThis study aims to understand the eHealth literacy skills of chronic patients and to explore the relations, patterns between eHealth literacy skills and different factors such as demographics, search strategies and health information sources and to explain their effects on eHealth literacy in Turkey in Izmir in COVID-19 outbreak.Design/methodology/approachA quantitative method was used in the study including a questionnaire. A total of 604 chronic patients responded to the questionnaire who applied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
(115 reference statements)
2
7
0
Order By: Relevance
“…Furthermore, in the studies of Jung et al (62) and Bak et al (63) it was reported that eHealth literacy was associated with age negatively. Also, the findings of Yuce et al were in line with those (57). On the other hand, Mitsutake et al (36) and Xesfingi and Vozikis (37) found a positive association between age and DHL levels.…”
Section: Digital Health Literacy and Sociodemographic Factorssupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, in the studies of Jung et al (62) and Bak et al (63) it was reported that eHealth literacy was associated with age negatively. Also, the findings of Yuce et al were in line with those (57). On the other hand, Mitsutake et al (36) and Xesfingi and Vozikis (37) found a positive association between age and DHL levels.…”
Section: Digital Health Literacy and Sociodemographic Factorssupporting
confidence: 66%
“…Moreover, studies conducted during COVID-19 period, Rivadeneira et al (54) and Dadaczynski et al (56) found higher digital health literacy scores in male groups. On the other hand, Zakar et al (52), Yuce et al (57), and Holt et al (58) revealed that females had higher DHL levels than males. Also, several studies have found no significant correlation between gender and DHL score (37,59).…”
Section: Digital Health Literacy and Sociodemographic Factorsmentioning
confidence: 98%
“…Facebook and Twitter were found to be significant predictors of eHealth literacy scores. Nevertheless, eHealth literacy was significantly reliant on digital literacy (Yuce et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In support of the views expressed by Cox et al (2022) and Camhi et al (2020), Safdieh et al (2021) add that medical student training in the telehealth space have been on the rise in recent years. Yuce (2022) suggests that digital literacy, particularly searching for information has an indirect effect on eHealth literacy. Digital literacy skills are essential in ensuring that society is able to search for relevant health information effectively.…”
Section: Telehealth and Covid-19 Contextmentioning
confidence: 99%
“…Yuce (2022) suggests that digital literacy, particularly searching for information has an indirect effect on eHealth literacy. Digital literacy skills are essential in ensuring that society is able to search for relevant health information effectively.…”
Section: Telehealth and Covid-19 Contextmentioning
confidence: 99%